2011
DOI: 10.1016/j.biochi.2011.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for both pro- and anti-inflammatory response induced by mannose-specific legume lectin from Cymbosema roseum

Abstract: Legume lectins, despite high sequence homology, express diverse biological activities that vary in potency and efficacy. In studies reported here, the mannose-specific lectin from Cymbosema roseum (CRLI), which binds N-glycoproteins, shows both pro-inflammatory effects when administered by local injection and anti-inflammatory effects when by systemic injection. Protein sequencing was obtained by Tandem Mass Spectrometry and the crystal structure was solved by X-ray crystallography using a Synchrotron radiatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 32 publications
0
17
0
1
Order By: Relevance
“…Some Phaseoleae lectins, isolated from Canavalia grandiflora , C. ensiformis [56], Dioclea rostrata [ 55 ], C. brasiliensis , C. gladiata , C. maritima (Assreuy et al ., 2009) and Cymbosema roseum [57], elicit inflammatory responses that could be reversed by specific carbohydrates. Cymbosema roseum is also known to elicit anti-inflammatory responses after systemic administration, which has been described as a legume lectin pattern of action; an inflammatory response based on administration route [57]. Cbol anti-inflammatory action is very consistent because describes anti-inflammatory responses through the i.v.…”
Section: Resultsmentioning
confidence: 99%
“…Some Phaseoleae lectins, isolated from Canavalia grandiflora , C. ensiformis [56], Dioclea rostrata [ 55 ], C. brasiliensis , C. gladiata , C. maritima (Assreuy et al ., 2009) and Cymbosema roseum [57], elicit inflammatory responses that could be reversed by specific carbohydrates. Cymbosema roseum is also known to elicit anti-inflammatory responses after systemic administration, which has been described as a legume lectin pattern of action; an inflammatory response based on administration route [57]. Cbol anti-inflammatory action is very consistent because describes anti-inflammatory responses through the i.v.…”
Section: Resultsmentioning
confidence: 99%
“…It has also been shown that legume lectins can be proinflammatory when administrated subcutaneously or anti-inflammatory when this administration is intravenous [20]. Alencar and coworkers [39] demonstrated that legume lectins act in inflammatory process via carbohydrate recognition domain (CDR), but AFAL is also capable of acting in a different way based on its affinity by CGN.…”
Section: Discussionmentioning
confidence: 99%
“…This sulfated polysaccharide has been used to test inflammation and anti-inflammatory activity with lectins for long time, but little can be deduced about how this activity occurs [4143]. Some authors assumed that some anti-inflammatory events, such as inhibition of neutrophil migration, occur through competition for binding to neutrophils between lectins tested and selectins [20, 39], but AFAL also can inhibit the signaling pathway triggered by CGN through the recognition and binding, preventing the recognition of carrageenan by epithelial cells and inhibiting the induction of IL-8 production resulted from the activation of BCL10 [23, 25]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A considerable number of marine invertebrate lectins have already been purified and characterized, and considerable attention is focused on its biological recognition role [8][9][10][11][12]. The Table I summarizes the origin, specificity, and biological activity from some lectins [5,[17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35]. Then, they come as ancestral molecules that show a high degree of conservation during the evolution to superior vertebrates [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%